Sistem Pakar Diagnosa Hama Penyakit Tanaman Padi Dan Holtikultura Menggunakan Metode Forward Chaining Berbasis Android - Frengki Pernando; Ahmad Fauzi (JURNAL TEKNIK KOMPUTER, 2019)
The development of information and communication technology-based smartphones and mobilephone growing rapidly. It is characterized by the number of smartphone users in the community. Utilization of information and communication technology is implemented in the form of knowledge application. One of these applications on the world agricultural expert system based on mobile. Knowledge of this expert system has many sources including research or research and observations that have been practiced by experts and issued either through web resources and other sources such as agricultural books, journals and others. This expert system uses Forward Chaining method using base database organized into a table in a rule that an expert and user can draw conclusions from what has been diagnosed by this expert system. Application of expert system designed and developed as an expert tools and users in diagnosing pests and diseases of rice plants and horticulture of the analysis by an expert and analysis according to the book or internet media. This expert system will show the questions will then be selected by the user to find a solution on the diagnostics program that has been done on this expert system. In addition the expert system is equipped with the paperwork to determine how plant pest management, plant species and type of fertilizer.